The problem of ethnic interpretation of archaeological cultures and the ethnogenesis of the Abkhaz-Adygs - Lina Kh. Guchapsheva; Vladimir A. Fomenko (Кавказология, 2024)
The article considers the problems of ethnic interpretation of archaeological cultures. The status of the concept of “archaeological culture” and the issue of the relationship between archaeological cultures and ethnic communities are analyzed because of both established theoretical approaches and modern ones. The system of ancient cultures of the Central and Western Caucasus is studied, which most adequately reflects the ethnic map of the Early Bronze Age. The problems of ethnogenesis and early stages of the ethnic history of the Abkhaz-Adyghe are considered in close connection with the archaeological cultures: Maikop and dolmen. This study addresses the issues of attributing archaeological cultures to specific ethnic groups, highlighting the deep roots of Abkhaz-Adyghe genesis and history, tracing them back not only to the Bronze Age but also to preceding eras. Various approaches and directions are analyzed, revealing the features of the origin and development of the Maikop and dolmen cultures, attention is focused on the presence of a large amount of scientific and factual material indicating the genetic and ethnocultural relationship of the bearers of the Early and Middle Bronze Age cultures with the proto-Abkhaz ethnic massif.